2012
DOI: 10.1016/j.exppara.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antileishmanial and antitrypanosomal activities of flavanones from Baccharis retusa DC. (Asteraceae)

Abstract: Leishmaniasis and Chagas' are parasitic protozoan diseases that affect the poorest population in the world, causing a high mortality and morbidity. As a result of highly toxic and long-term treatments, novel, safe and more efficacious drugs are essential. In this work, the CH(2)Cl(2) phase from MeOH extract from the leaves of Baccharis retusa DC. (Asteraceae) was fractioned to afford two flavonoids: naringenin (1) and sakuranetin (2). These compounds were in vitro tested against Leishmania spp. promastigotes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 28 publications
5
48
0
1
Order By: Relevance
“…In another report, this flavanone isolated from Baccharis retusa showed in vitro activity against T. cruzi trypomastigotes (IC 50 20.2 µg mL -1 ) (Grecco et al 2012). Similar results were observed for sakuranetin (5) in our experiments against epimastigote forms of T. cruzi Y strain (IC 50 47.5 µg mL -1 , Table 2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In another report, this flavanone isolated from Baccharis retusa showed in vitro activity against T. cruzi trypomastigotes (IC 50 20.2 µg mL -1 ) (Grecco et al 2012). Similar results were observed for sakuranetin (5) in our experiments against epimastigote forms of T. cruzi Y strain (IC 50 47.5 µg mL -1 , Table 2).…”
Section: Discussionsupporting
confidence: 79%
“…It is noteworthy that such flavonoids were previously detected in the ethanol extract from L. sidoides leaves and might therefore be related to its leishmanicidal activity (Funari et al 2012a). Grecco et al (2012) reported IC 50 51.9 µg mL -1 for sakuranetin (5) isolated from Baccharis retusa against promastigotes of L. amazonensis, which is similar to the results from our experiments against the same type of protozoa (Table 2). Asebogenin (3) isolated from an extract of Piper elongatum aerial parts was described by Hermoso et al (2003) as more active against promastigote forms of L. braziliensis, L. tropica and L. infantum (IC 50 28.5, 3.8 and 6.3 µg mL -1 , respectively) than the observed inhibition against L. amazonensis promastigotes (IC 50 47.5 µg mL -1 , Table 2) in our experiments.…”
Section: Leishmanicidal Activitysupporting
confidence: 81%
“…The tested extracts/ compounds were added up to 200 lg/mL concentration while groups from bioactivity-guided fractionation were tested at unique concentration (200 lg/mL). After incubation for 48 h at 24 C, the viability of promastigotes was verified by the colorimetric MTT assay (Grecco et al 2012). Promastigotes incubated without compounds were used as control (100% viability) and wells without cells as blank.…”
Section: Determination Of the Activity Against L Infantumpromastigotesmentioning
confidence: 99%
“…Despite this knowledge, few studies have evaluated biological activity of 'carnauba' wax, including defensive proteins with antifungal activity (Cruz et al 2002). As part of our continuous project involved in the discovery of antiprotozoal compounds from Brazilian plant species (Grecco et al 2012;Rea et al 2013;Morais et al 2014;Costa-Silva et al 2015), the present work was aimed to identify antiprotozoal metabolites of C. prunifera wax (types 1 and 4) as well as the evaluation of their mammalian cytotoxicity. As a result, three bioactive dammarane-type triterpenoids: (24R Ã )-methyldammar-25-ene-3b,20-diol (carnaubadiol, 1), (24R Ã )-methyldammara-20,25-dien-3-one (2) and (24R Ã )-methyldammara-20,25-dien-3a-ol (3) were characterized.…”
Section: Introductionmentioning
confidence: 99%
“…21 Also, these drugs are ineffective against the chronic phase of the disease demonstrating the urgent need for new drugs. 20 In our continuing search for anti-parasitic natural products from Brazilian plants, [22][23][24] the crude MeOH extract from leaves of P. barbatus displayed in vitro anti-trypanosomal activity and was subjected to bioactivity-guided fractionation. Using several chromatographic procedures, the compound 1,2,3,4,6-penta--O-galloyl-b-D-glucose (PGG) was isolated for the first time in the Plectranthus genus, identified after NMR and LRESIMS analysis.…”
Section: Introductionmentioning
confidence: 99%